Comments of the AFAANZ auditing and assurance standards committee on proposed international standard on auditing ISA for LCE. (13th June 2022) - Coram, Paul J.; Fu, Yi (Dale); Garg, Mukush; Harding, Noel; Hay, David C.; Khan, Mohammad Jahanzeb; Muñoz‐Izquierdo, Nora; Prasad, Ashna; Sultana, Nigar; Tong, Jamie
Abstract: The International Auditing and Assurance Standards Board (IAASB) issued for public comment Proposed International Standard on Auditing for Audits of Financial Statements of Less Complex Entities (ISA for LCE). The Australian Auditing and Assurance Standards Board (AUASB) and New Zealand Auditing and Assurance Standards Board (NZAuASB) also called for comments. The Auditing and Assurance Standards Committee of the Accounting and Finance Association of Australia and New Zealand (AFAANZ) prepared a submission, based on the findings reported in extant research, informing a number of the questions asked by the IAASB (and AUASB/NZAuASB). This commentary presents the formal submission made to the IAASB.